PA 07-3-2276 Expert perspectives on paediatric burn recovery needs, challenges and coping trajectories. (November 2018) - Niekerk, Ashley van; Jacobs, Roxanne; Hornsby, Nancy; Singh, Robyn
Abstract : Burn injuries are among the most painful experiences for a child and may result in long-term physical, emotional and social consequences. Recovery from burns is a complex psycho-social process for children and their families. Early supportive interventions are considered important, however there is a paucity of information on burn recovery immediately post-discharge, especially in societies with constrained support services and high levels of stigmatisation. This study describes, from the perspectives of South African burn recovery experts, the psychosocial needs of paediatric burn victims aged 10 to 15 years with a focus on the acute phase of burn care and the first three months post-injury. The following is addressed: the psychosocial challenges faced by children after a burn; the resiliency skills that support coping; and the child and family support needs observed. The study involved 11 semi-structured interviews with service providers working with paediatric burn survivors and their caregivers. Verbatim interview transcripts are currently being independently analysed by two researchers, with qualitative thematic analysis used to extract common themes. Initial analyses indicate that child burn victims were reported to encounter, during the acute and post-discharge phases, physical and emotional pain, with various degrees of depression, anxiety, sleep disturbance, social withdrawal and fear (including anticipatory fear connected with appearance changes). Grief was commonly reported by both children and caregivers, over the loss of the child's 'former' self, with concerns about stigmatisation and rejection from family, friends and strangers. The child's personality, self-confidence and self-acceptance, and family stability was reported to be key to initial resiliency. With discharge the acceptance from siblings, family, friends, and teachers were highlighted as important. The recovery process is a complex and interactive one with a range of internal and external enablers that may be support recovery.